Supervised Internship in the training of Mathematics teachers, in the distance modality: reflexes of the pandemic - Araújo, Helenice Maria Costa (2021)
In this text, we present the results of a study carried out through a qualitative research of the case study type, whose objective was to analyze the changes that occurred in the curricular component of Supervised Internship, in the Licentiate Degree in Mathematics, in the distance modality, at the University Federal de Uberlândia, in the context of the COVID 19 pandemic. We based on the conceptualization of pedagogical models known as Pedagogical Architecture to analyze the data generated in the study, organized by four aspects: organizational, instructional or content, methodological and technological. We highlight the following points as results: (i) strengthening in the teacher trainer/supervisory teacher/trainee relationship; (ii) a change in the supervising teacher's attitude; (iii) the student-intern being the center of interactions; (iv) greater diffusion of technology. These points help us to reaffirm that the curricular internship is a space where it privileges the learning of the future teaching profession.